NYPD red - Patterson, James, 1947-; Karp, Marshall (New York : Little, Brown and Co., 2012)
Detective Zach Jordan investigates a series of public crimes that coincide with the arrival of dozens of glamorous celebrities in town for parties and premieres. NYPD Red is a special task force charged with protecting the interests of Manhattan's wealthiest and most powerful citizens. When a world-famous movie producer is poisoned on the first day of a Manhattan film festival they are the first ones called.
Keywords: Murder -- Investigation -- New York (State) -- New York -- Fiction; Motion pictures -- Production and direction -- New York (State) -- New York -- Fiction; Mystery fiction